The complete plastome of Peucedanum praeruptorum (Apiaceae) - Yingshuo Li; Maolin Geng; Zenglai Xu; Qiong Wang; Lingli Li; Ming Xu; Mimi Li (Mitochondrial DNA. Part B. Resources, 2019)
Peucedanum praeruptorum is an important traditional herbal medicine unique to China. The complete chloroplast genome of P. praeruptorum was generated here using high-throughput sequencing. The plastome was 147,197 bp in size, which consisted of a pair of inverted repeats (IRs; 18,713 bp), a large single copy (LSC; 92,161 bp) and a small single copy (SSC; 17,610 bp). The GC content of the plastome was 37.6%, with 44.5%, 36.0%, and 31.1% in IRs, LSC, and SSC, respectively. A total of 128 genes were annotated, including 84 protein-coding genes, 35 tRNAs, eight rRNAs, and one pseudogene (Ψycf1). The phylogenomic analysis indicated that P. praeruptorum formed a monophyletic clade with Peucedanum japonicum.